Strength training for the brain: Using technology to deliver mindfulness training to improve strength and conditioning performance - Rist, B.; Pearce, A. J. (Strength and Conditioning Journal, 2016)
This article examines the benefits of using mindfulness through technology to enhance strength and conditioning (sc) training performance. Although the effectiveness of mindfulness has been demonstrated in athletes from novice to collegiate levels, athletes continue to fail to use mindfulness citing a range of issues including time demands and expense of psychologists. One solution may be through using technology to explore smartphone applications that can deliver mindfulness training before and during sc sessions. It is proposed that the use of smartphone technology may bridge the gap that exists in past methods of delivery of mindfulness interventions. For a video abstract describing this article, see, supplemental digital content 1, (see video, http://links.lww.com/scj/a197).